The influence of maternal gestational weight gain on adverse perinatal outcomes - Yan, Qingshan; Cai, Wenya; Guo, Yong (Frontiers in Endocrinology, 2025)
ObjectiveTo analyze the impact of maternal gestational weight gain (GWG) on adverse outcomes for mothers and infants.MethodsA retrospective analysis was conducted, collecting relevant information on 9,058 singleton pregnancies and newborns from prenatal check-ups and deliveries at Guangdong Women and Children Hospital from 2017 to 2022. The subjects were grouped according to different GWG, and logistic regression was used to analyze the impact of GWG on adverse outcomes, including hypertensive disorders of pregnancy (HDP), gestational diabetes mellitus (GDM), large-for-gestational-age infants (LGA), small-for-gestational-age infants (SGA), and preterm births.ResultsAmong the 9058 participants included in the study, there were 438 cases (4.8%) of HDP, including 266 cases (2.9%) of gestational hypertension and 172 cases (1.9%) of preeclampsia. Additionally, there were 2018 cases (22.3%) of GDM; Among the adverse birth outcomes for newborns, the prevalence was 9.7% for SGA, 9.9% for LGA, 1.4% for early/mid-term preterm births, and 4.2% for late preterm births. After adjusting for confounding factors, the results showed that, excessive GWG was a risk factor for HDP (OR=1.829, P<0.05) and LGA (OR=1.792, P<0.05) compared to the normal gestational weight gain group. Insufficient GWG increased the risk of GDM (OR=2.203, P<0.05), SGA (OR=1.474, P<0.05) and was also a risk factor for early/mid-term preterm infants (OR=3.326, P<0.05) and late preterm infants (OR=1.715, P<0.05).ConclusionExcessive GWG is a risk factor for the occurrence of HDP and LGA, while insufficient GWG increases the risk of GDM, SGA and preterm infants (especially early/mid-term preterm infants). Therefore, it is recommended to strengthen the monitoring of weight changes during pregnancy in women of childbearing age, guide nutritional management during pregnancy, and keep GWG within a reasonable range to prevent adverse outcomes for mothers and infants.